Optimized Infrared LED and Its Use in an All‐HgTe Nanocrystal‐Based Active Imaging Setup. Issue 4 (13th December 2021) - Bossavit, Erwan; Qu, Junling; Abadie, Claire; Dabard, Corentin; Dang, Tung; Izquierdo, Eva; Khalili, Adrien; Gréboval, Charlie; Chu, Audrey; Pierini, Stefano; Cavallo, Mariarosa; Prado, Yoann; et al.
Abstract: Nanocrystals (NCs) have reached a high level of maturity, enabling their integration into optoelectronic devices. The next challenge is the combination of several types of devices into one complex system to achieve better on‐chip integration. Here, an all‐HgTe‐NC active imaging setup operating in the short‐wave infrared (IR) is focused on. First, the design of an optimized IR light‐emitting diode (LED) is focused on. It is shown that a halide technology processing enables an increase of the electroluminescence signal by a factor of 3, while preserving a low turn‐on voltage and a high brightness (3 W sr −1 m −2 ). Then the degradation mechanism of this LED under continuous operation is unveiled and a shift from band edge to trap emission is shown. This degradation process can be strongly reduced thanks to the encapsulation and the thermal control of the LED. Lastly, the IR emission of the LED is imaged using a focal plane array whose active layer is also made of HgTe NCs, paving the way for all‐NC‐based active imaging setups. Abstract : An HgTe‐nanocrystal‐based light‐emitting diode (LED) with shortwave infrared (IR) emission is designed. The HgTe‐nanocrystal‐based camera imaging this LED provides IR images of the operating pixels (as shown in the inset).